Comparative Perspectives Database - Gender & Work Database - York University. Department of Politics; Vosko, Leah F. (2014)
The Comparative Perspectives on Precarious Employment Database (CPD) brings together a library of relevant sources, unique user-friendly statistical tables, and a thesaurus of concepts – designed to facilitate research on labour market insecurity in a comparative industrialized context. Users can analyze multidimensional tables to explore and compare the contours of precarious employment in thirty-three countries, including Australia, Canada, the United States, twenty-seven European Union (EU) member countries and three non-European Union member countries. ...The introduction provides basic information on the CPD’s conceptual approach to precarious employment in a comparative perspective, an explanation of CPD methodology, and an outline of the design principles behind the creation of harmonized variables used in the statistical tables. These principles are further developed and demonstrated in three interactive modules: forms of precarious employment, temporal and spatial dynamics, and health and social care. --Website description